HUBUNGAN KECERDASAN INTELEKTUAL, KOORDINASI MATA TANGAN DAN KEPERCAYAAN DIRI TERHADAP KETERAMPILAN PASSING ATAS - Oktaviati, Ririn; Sudrajat, Adang; Setia Lengkana, Anggi (STKIP Muhammadiyah Kuningan, 2024)
Volleyball games are included in team games, therefore a mastery of technique, mental/psychological factors, and individual intelligence is needed to produce good cooperation between team members, so as to produce their best performance. This research is based on a problem that researchers found in the field, namely the lack of mastery of basic overhead passing techniques. It can be seen that the resulting ball is not on target and is easily read by the opponent. Thus, this study aims to determine the relationship between intellectual intelligence, eye-hand coordination, and confidence in overhead passing skills. This type of research uses a quantitative approach with a correlational method. The population of this study is female athletes of volleyball clubs in North Sumedang sub-district. Sampling technique using purposive sampling so that samples that meet the criteria are 20 samples. Based on data processing using statistical tests assisted by IBM SPSS type 20 for windows software, it shows that: (1) There is no relationship between intellectual intelligence and overhead passing skills, (2) There is a relationship between eye-hand coordination and overhead passing skills, (3) There is a relationship between confidence in skills overhead passing, and (4) There is a simultaneous or shared relationship between intellectual intelligence, eye-hand coordination, and confidence in overhead passing skills with a correlation coefficient (R) of 0.625 and a coefficient of determination (R2) of 39%.